Learning Management Training Management System at STKIP Pacitan as an Effort to Increase Learning Effectiveness - Munir, Agus Qomaruddin; Wardani, Ratna; Nurkhamid, Nurkhamid; Setiyawan, Ramadhana; Mustofa, Zaenal (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2025)
STKIP Pacitan has adopted Moodle as its primary Learning Management System (LMS) to improve the quality of learning and teaching efficiency in the digital era. Adapting to educational technology requires the faculty's deep understanding and effective management skills. Therefore, Moodle management training was conducted to enhance the faculty's abilities in planning, targeting, and producing quality learning outcomes. Through interactive sessions and workshops, faculty members were taught how to design courses, organize content, and utilize Moodle's features for more dynamic and participatory learning activities. The main focus of the training was on integrating assessment tools and discussion forums to enhance interaction and effective feedback. The training evaluation was conducted by measuring the faculty's performance before and after the training using indicators of course planning quality and evaluation tools. The training successfully demonstrated that the use of Moodle not only supports the efficiency of the teaching and learning process but also improves the quality of education at STKIP Pacitan, with increases of 27%, 68%, and 77% over three months in May, June, and July 2024, respectively. In addition, several applied learning methods positively impact students; feedback to students is increasingly focused (LMS record), which shows that learning effectiveness is increasing. This training recommends ongoing training to ensure optimal utilization of educational technology and continuous adaptation to the latest developments in educational technology.